Development strategies for tourism industry - Peterson, Donald (Clanrye International, 2015)
Tourism is a major economic contributor. This book provides extensive information regarding the strategies adopted by stake holders in the tourism industry. We have been witnessing huge competition among the organizations in the business world. Companies are looking for resourceful methods to participate in the global tourism market. In business, the major objective is to make profit. However, if the focus is only on profit, it will not to be easy for them to succeed. It is more significant for organizations to find out how to make a well-built strategy in order to be more competitive in the marketplace. More and more organizations have been using pioneering approaches to reinforce their position. Creative working enables organizations to make their position more competitive and be more value-oriented in the global tourism industry. This book is a compilation of various case studies regarding the impact of tourism business strategies accomplished over the years. It presents case studies which illustrate diverse development strategies viable for tourism industries.